Preparation and application of carbon dots using polyamide as precursor
The preparation of high fluorescence intensity carbon dots through one-step reaction between polyamide and crosslinking agent, solves the problems of textile waste utilization and metal ion detection, realizes the dual benefits of environmental protection and resource utilization, and has broad application prospects.
Patent Information
- Application Number
- CN202111159232.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-30
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2041-09-30
AI Technical Summary
The prior art is difficult to effectively utilize textile waste and solve the problems of environmental pollution and oil resource depletion, and at the same time, it lacks a simple, efficient and accurate method to detect metal ion content.
Polyamide is used as a carbon source and a crosslinking agent to prepare carbon dots with high fluorescence intensity, and the linear relationship between its fluorescence intensity and Fe3+ content and pH value is used to achieve the detection of Fe3+ and pH.
It realizes efficient utilization of textile waste, provides a new treatment method, has good fluorescence imaging performance and thermal stability, and can be used in the fields of fluorescence detection and anti-counterfeiting.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to a novel fluorescent carbon nanomaterial, and in particular to the preparation and application of carbon dots using nylon 66 as a precursor. Background Art
[0002] Carbon dots (CDs) are a new type of fluorescent material with nanoscale, mainly composed of carbon elements. Its essential characteristics are that the size in at least one dimension is less than 10nm and it has the property of photoluminescence. Since it was first reported in 2004, carbon dots have been widely studied due to their low toxicity, good biocompatibility, and excellent optical properties. They have shown great advantages in different fields such as fluorescent probes, biomedicine and imaging, optoelectronic devices, and photocatalysis. Recently, researchers have discovered a new type of carbon dots with high fluorescence quantum yield - carbonized polymer dots (CPDs). This new type of carbon dots is prepared from certain small molecules or polymers through dehydration condensation, crosslinking and carbonization processes. Carbonized polymer dots are considered to be a new type of carbon dots with a low degree of carbonization because they have the structure of traditional carbon dots (carbon core) and polymers (polymer chains). Compared with traditional carbon dots, carbonized polymer dots have attracted widespread attention due to their high oxygen content, good water solubility and high quantum yield.
[0003] Due to the growth of the world population and the improvement of living standards, global fiber consumption has been growing steadily in the past few decades, resulting in a sharp increase in textile waste. If textile waste is simply landfilled or incinerated, it will not only cause environmental pollution problems but also deplete petroleum resources. Therefore, how to make full use of textile waste is of great significance. Carbon dots, as a new type of fluorescent nano-scale material, are mainly composed of elements such as C, O, and H, among which the content of C element is generally high. Therefore, substances containing C elements have the potential to become carbon dot precursors, and textile waste is essentially a polymer containing a large amount of carbon elements, so it has the potential to become a carbonized polymer precursor. In a sense, the preparation of carbonized polymer dots using textile waste as a precursor can not only alleviate the problems of environmental pollution and depletion of petroleum resources, but also further increase the added value. To a certain extent, waste utilization has a high research value.
[0004] Studies have shown that iron ions are an indispensable substance in the human body and an important component of hemoglobin. They can participate in many metabolic activities in the human body and play an important role in them. If the human body is iron deficient, it may cause iron deficiency anemia. At the same time, with the improvement of living standards, people's requirements for water quality have also been further improved. How to simply, efficiently and accurately detect the content of metal ions and find a convenient metal ion sensor is of great significance. Summary of the invention
[0005] Based on the above technical background, the inventors have made great progress and found that: by using polyamide as a carbon source and reacting with a cross-linking agent in one step, carbon dots with high fluorescence intensity can be obtained, which can not only solve the problems of environmental pollution and oil resource depletion caused by landfill of polyamide waste textiles, but also have stable optical properties. The fluorescence intensity of the carbon dots is similar to that of Fe 3+ The content and pH are linearly correlated and can be used for Fe 3+ The detection of content and pH also has good application prospects in fluorescence imaging. Using polyamide as a carbon source also provides a new treatment method for polyamide waste, thereby completing the present invention.
[0006] The first aspect of the present invention is to provide a polyamide-based carbon dot, which is prepared from polyamide and a cross-linking agent;
[0007] The fluorescence intensity of the polyamide-based carbon dots is similar to that of Fe 3+ The fluorescence intensity is linearly related to the pH value.
[0008] The second aspect of the present invention is to provide a method for preparing the polyamide-based carbon dots according to the first aspect of the present invention, the preparation method comprising the following steps:
[0009] Step 1, mixing polyamide and a cross-linking agent and heating them to react;
[0010] Step 2: Filter the product obtained in step 1 to obtain polyamide-based carbon dots.
[0011] The third aspect of the present invention is to provide the use of the polyamide-based carbon dots according to the first aspect of the present invention and the polyamide-based carbon dots prepared by the preparation method according to the second aspect of the present invention, which can be used to prepare fluorescent ink, fluorescent powder, fluorescent agar gel, and can also be used for pH and Fe 3+ Content detection and anti-counterfeiting field.
[0012] The preparation method of carbon dots using polyamide as a precursor and the application thereof provided by the present invention have the following advantages:
[0013] (1) The fluorescence of the polyamide-based carbon dots of the present invention is dependent on the excitation wavelength and has a high fluorescence intensity;
[0014] (2) The polyamide-based carbon dots of the present invention use polyamide as a carbon source, which can not only alleviate the problems of environmental pollution and oil resource depletion, but also provide a new treatment method for polyamide waste;
[0015] (3) The preparation method of the polyamide-based carbon dots of the present invention is simple, and the carbon dots can be used for the detection of pH and iron ions, and also have good thermal stability and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The transmission electron microscopy image and particle size distribution diagram of the polyamide-based carbon dots prepared in Example 13 are shown;
[0017] Figure 2 The infrared spectrum of the polyamide-based carbon dots prepared in Example 13 is shown;
[0018] Figure 3 The fluorescence spectra of the polyamide-based carbon dots prepared in Examples 1 to 4 and the comparative example are shown;
[0019] Figure 4 The fluorescence spectra of the polyamide-based carbon dots prepared in Example 1 and Examples 5 to 9 are shown;
[0020] Figure 5 The fluorescence spectra of the polyamide-based carbon dots prepared in Example 7 and Examples 10 to 12 are shown;
[0021] Figure 6 The fluorescence spectra of the polyamide-based carbon dots prepared in Example 7 and Examples 13 to 15 are shown;
[0022] Figure 7 The fluorescence lifetime distribution diagram of the polyamide-based carbon dots prepared in Example 13 is shown;
[0023] Figure 8 The fluorescence quantum yield spectrum of the polyamide-based carbon dots prepared in Example 13 is shown;
[0024] Fig. 9 A histogram showing the fluorescence intensity of the polyamide-based carbon dots prepared in Example 13 after adding different metal ions;
[0025] Fig.10 The fluorescence spectra of the polyamide-based carbon dots prepared in Example 13 under different pH conditions are shown;
[0026] Fig.11 A graph showing the relationship between the fluorescence intensity of the polyamide-based carbon dots prepared in Example 13 and the corresponding pH;
[0027] Fig.12 The photos of the polyamide-based carbon dot phosphor prepared in Example 13 under natural light and ultraviolet light are shown;
[0028] Fig.13 The fluorescence intensity of the polyamide-based carbon dots prepared in Example 13 is shown in Figure 13 and the corresponding Fe 3+ Concentration relationship diagram. DETAILED DESCRIPTION
[0029] The present invention will be described in detail below, and the characteristics and advantages of the present invention will become clearer and more distinct with the description.
[0030] The first aspect of the present invention is to provide a polyamide-based carbon dot, wherein the polyamide-based carbon dot is prepared from polyamide and a cross-linking agent.
[0031] The polyamide is selected from one or more of polyhexamethylene adipamide (PA-66), polyhexamethylene sebacamide (PA-610), polydecanediamine sebacamide (PA-1010), polycaprolactam (PA-6), polyhexamethylene lauroyl (PA-612) and polylaurolactam (PA-12), preferably selected from one or more of polyhexamethylene adipamide, polydecanediamine sebacamide and polycaprolactam, more preferably polyhexamethylene adipamide.
[0032] Polyamide is a polymer containing a large amount of carbon elements. The use of polyamide as a carbon source for the preparation of carbon dots can not only solve the environmental pollution caused by landfill of waste textiles and the depletion of oil resources, but also increase its added value and bring certain economic benefits. The inventors found that the use of the above polyamide as a carbon source can obtain carbon dots with high fluorescence intensity and long fluorescence lifetime, and also has good thermal stability. Not only can it be used in fluorescence imaging, its fluorescence intensity is also related to pH and Fe 3+ The content is linear and can also be used for pH and Fe 3+ The detection has broad application prospects.
[0033] The cross-linking agent is selected from one or more of hexachlorocyclotriphosphazene (HCCP), potassium perfluorobutylsulfonate (OSS), diisopropyl benzene peroxide, benzoyl peroxide, diisopropyl benzene hydroperoxide, diethylaminopropylamine, formaldehyde, glyoxal, malondialdehyde, succindialdehyde, glutaraldehyde, concentrated sulfuric acid and concentrated phosphoric acid, preferably selected from one or more of hexachlorocyclotriphosphazene, potassium perfluorobutylsulfonate, diisopropyl benzene peroxide, benzoyl peroxide, glutaraldehyde and concentrated phosphoric acid, and more preferably selected from one or more of hexachlorocyclotriphosphazene, potassium perfluorobutylsulfonate, glutaraldehyde and concentrated phosphoric acid.
[0034] The mass ratio of the crosslinking agent to the polyamide is (0.01-0.8):1, preferably (0.05-0.7):1, and more preferably (0.1-0.6):1.
[0035] The polyamide-based carbon dots of the present invention are spherical and have a particle size of 1.6 to 3.5 nm. -1 It has the characteristic absorption peak of OH and the stretching vibration peak of NH, 3060cm -1 The secondary amide NH stretching vibration peak is 2930 cm -1 and 2850cm -1 The absorption peaks at 1630 cm-1 are saturated CH asymmetric stretching vibration and saturated CH symmetric stretching vibration. -1 and 1540cm -1The characteristic absorption peak at 1280cm is the C=O stretching vibration peak. -1 The peak at 691 cm is the secondary amide CN stretching vibration peak. -1 The peak at is the bending vibration peak of the OC=O group.
[0036] The fluorescence quantum yield of the polyamide-based carbon dots is 20-25%. 3+ The fluorescence quenching of the polyamide-based carbon dots is significant, and they hardly respond to other metal ions. 3+ The concentration of Fe 3+ Fluorescence detection.
[0037] The polyamide-based carbon dots of the present invention have different fluorescence intensities at different pH values, and the fluorescence intensity is linearly correlated with the pH value, and can be used to detect the pH value of a solution.
[0038] The second aspect of the present invention is to provide a method for preparing the polyamide-based carbon dots according to the first aspect of the present invention, the preparation method comprising the following steps:
[0039] Step 1, mixing polyamide and a cross-linking agent and heating them to react;
[0040] Step 2: Filter the product obtained in step 1 to obtain polyamide-based carbon dots.
[0041] This step is described and illustrated in detail below.
[0042] Step 1: Mix polyamide and a cross-linking agent and heat them to react.
[0043] The polyamide is selected from one or more of polyhexamethylene adipamide (PA-66), polyhexamethylene sebacamide (PA-610), polydecanediamine sebacamide (PA-1010), polycaprolactam (PA-6), polyhexamethylene lauroylamine (PA-612) and polylaurolactam (PA-12), preferably selected from one or more of polyhexamethylene adipamide, polydecanediamine sebacamide and polycaprolactam, more preferably polyhexamethylene adipamide.
[0044] The cross-linking agent is selected from one or more of hexachlorocyclotriphosphazene (HCCP), potassium perfluorobutylsulfonate (OSS), diisopropyl benzene peroxide, benzoyl peroxide, diisopropyl benzene hydroperoxide, diethylaminopropylamine, formaldehyde, glyoxal, malondialdehyde, succindialdehyde, glutaraldehyde, concentrated sulfuric acid and concentrated phosphoric acid, preferably selected from one or more of hexachlorocyclotriphosphazene, potassium perfluorobutylsulfonate, diisopropyl benzene peroxide, benzoyl peroxide, glutaraldehyde and concentrated phosphoric acid, and more preferably selected from one or more of hexachlorocyclotriphosphazene, potassium perfluorobutylsulfonate, glutaraldehyde and concentrated phosphoric acid.
[0045] The experiment found that the cross-linking agent will also affect the fluorescence intensity of the polyamide-based carbon dots. The fluorescence intensity of the polyamide-based carbon dots prepared by using the above cross-linking agent is much greater than the fluorescence intensity of the carbon dots prepared by other cross-linking agents.
[0046] The mass ratio of the crosslinking agent to the polyamide is (0.01-0.8):1, preferably (0.05-0.7):1, and more preferably (0.1-0.6):1.
[0047] The amount of cross-linking agent used will affect the fluorescence intensity of polyamide-based carbon dots. As the amount of cross-linking agent increases, the fluorescence intensity of the carbon dots gradually increases. However, after a certain amount of cross-linking agent is added, the fluorescence intensity of the carbon dots gradually tends to be stable. When the amount of cross-linking agent continues to increase, the fluorescence intensity of the carbon dots decreases slightly. When the amount of cross-linking agent added is within the above range, the fluorescence intensity of the carbon dots is the highest.
[0048] A solvent is also added during the mixing process, and the solvent is selected from one or more of an organic solvent and water, preferably one or two of acetic acid and water, and more preferably water. Water as a solvent is not only abundant in source, but also has a certain effect on environmental protection.
[0049] There is no limitation on the amount of solvent added. The inventors have found that the amount of solvent added has no effect on the fluorescence intensity of the prepared carbon dots. When the amount of solvent added is different, the fluorescence intensity of the prepared carbon dots is not much different.
[0050] The reaction is preferably carried out in a reaction vessel. In the present invention, the reaction temperature is 150 to 350°C, preferably 170 to 300°C, and more preferably 200 to 280°C.
[0051] As the reaction temperature increases, the fluorescence intensity of the polyamide-based carbon dots gradually increases, but if the reaction temperature continues to increase, the fluorescence intensity of the carbon dots will decrease. Experiments have found that the carbon dots have a higher fluorescence intensity when the reaction temperature is 200-280°C.
[0052] The reaction time is 5 to 60 hours, preferably 7 to 55 hours, and more preferably 10 to 50 hours.
[0053] It was found in the experiment that when the reaction time was greater than 10 hours, the sample was transparent and clear, and the insoluble precipitate disappeared. When the reaction time was further extended, the fluorescence intensity of the carbon dots gradually increased. However, after more than 50 hours, the fluorescence intensity of the carbon dots gradually decreased.
[0054] Step 2: Filter the product obtained in step 1 to obtain polyamide-based carbon dots.
[0055] After the reactor is cooled naturally, the product obtained in step 1 is filtered to remove large particles using a syringe filter.
[0056] The pore size of the filter membrane is 0.1-0.8 μm, preferably 0.2-0.45 μm, more preferably 0.22 μm, and is used to filter large particles.
[0057] The third aspect of the present invention is to provide the use of the polyamide-based carbon dots according to the first aspect of the present invention and the polyamide-based carbon dots prepared by the preparation method according to the second aspect of the present invention, which can be used to prepare fluorescent ink, fluorescent powder, fluorescent agar gel, and can also be used for pH and Fe 3+ Content detection and anti-counterfeiting field.
[0058] The beneficial effects of the present invention are:
[0059] (1) The polyamide-based carbon dots described in the present invention are spherical, with a particle size of 1.6 to 3.5 nm, and are evenly distributed without agglomeration;
[0060] (2) The fluorescence of the polyamide-based carbon dots of the present invention is dependent on the excitation wavelength, and has a high fluorescence intensity, a fluorescence quantum yield of up to 21.38%, and an average fluorescence lifetime of 13.57 ns;
[0061] (3) The polyamide-based carbon dots prepared in the present invention are light yellow under natural light and emit bright blue fluorescence under ultraviolet light;
[0062] (4) The polyamide-based carbon dots prepared in the present invention have an effect on Fe 3+ The fluorescence quenching of α-H2O is significant, and it hardly responds to other metal ions, indicating that it is not easily affected by the removal of Fe 3+ In order to avoid the interference of other metal ions, polyamide-based carbon dots can be used as fluorescent probes to detect Fe 3+ Content detection;
[0063] (5) The polyamide-based carbon dots prepared in the present invention have different fluorescence intensities at different pH values, and the fluorescence intensity of the carbon dots is linearly correlated with the pH value, indicating that the polyamide-based carbon dots can be used for pH detection;
[0064] (6) The polyamide-based carbon dots of the present invention can be applied to fluorescent inks, fluorescent powders, and fluorescent agar gels, indicating that the optical properties of the carbon dots are stable during heating and they can also emit light stably in the solid phase.
[0065] Example
[0066] The present invention is further described below by means of specific examples. These embodiments are only intended to illustrate the present invention but are not intended to limit the scope of the present invention.
[0067] Example 1
[0068] Add 0.5 g PA-66, 200 μL 50% glutaraldehyde and 25 mL deionized water into a 50 mL hydrothermal reactor. Tighten the reactor and place it in an oven. Set the reaction temperature to 240 °C and the reaction time to 12 h. After the reaction is completed, turn off the oven.
[0069] After the reaction kettle is cooled naturally, it is taken out and the prepared sample is filtered through a 0.22 μm syringe filter to obtain a PA-66-based carbon dot solution.
[0070] Example 2
[0071] The preparation of PA-66-based carbon dots was carried out in a similar manner to Example 1, except that 0.5 g PA-66, 0.1 g potassium perfluorobutanesulfonate and 25 mL deionized water were added to a 50 mL hydrothermal reactor.
[0072] Example 3
[0073] The preparation of PA-66-based carbon dots was carried out in a similar manner to Example 1, except that 0.5 g PA-66, 0.1 g hexachlorocyclotriphosphazene and 25 mL deionized water were added to a 50 mL hydrothermal reactor.
[0074] Example 4
[0075] The preparation of PA-66-based carbon dots was carried out in a manner similar to Example 1, except that 0.5 g PA-66, 53.4 μL of 85% concentrated phosphoric acid and 25 mL of deionized water were added to a 50 mL hydrothermal reactor.
[0076] Example 5
[0077] The preparation of PA-66-based carbon dots was carried out in a similar manner to Example 1, except that the amount of 50% by mass glutaraldehyde added was 100 μL.
[0078] Example 6
[0079] The preparation of PA-66-based carbon dots was carried out in a similar manner to Example 1, except that the amount of 50% by mass glutaraldehyde added was 300 μL.
[0080] Example 7
[0081] The preparation of PA-66-based carbon dots was carried out in a similar manner to Example 1, except that the amount of 50% by mass glutaraldehyde added was 400 μL.
[0082] Example 8
[0083] The preparation of PA-66-based carbon dots was carried out in a similar manner to Example 1, except that the amount of 50% by mass glutaraldehyde added was 500 μL.
[0084] Example 9
[0085] The preparation of PA-66-based carbon dots was carried out in a similar manner to Example 1, except that the amount of 50% by mass glutaraldehyde added was 600 μL.
[0086] Example 10
[0087] The preparation of PA-66-based carbon dots was carried out in a similar manner to Example 1, except that the amount of 50% by mass glutaraldehyde added was 400 μL, and the reaction temperature was 200°C.
[0088] Embodiment 11
[0089] The preparation of PA-66-based carbon dots was carried out in a similar manner to Example 1, except that the amount of 50% by mass glutaraldehyde added was 400 μL, and the reaction temperature was 220°C.
[0090] Example 12
[0091] The preparation of PA-66-based carbon dots was carried out in a similar manner to Example 1, except that the amount of 50% by mass glutaraldehyde added was 400 μL, and the reaction temperature was 260°C.
[0092] Embodiment 13
[0093] The preparation of PA-66-based carbon dots was carried out in a similar manner to Example 1, except that the amount of 50% glutaraldehyde added was 400 μL, and the reaction time was 24 h.
[0094] Embodiment 14
[0095] The preparation of PA-66-based carbon dots was carried out in a similar manner to Example 1, except that the amount of 50% by mass glutaraldehyde added was 400 μL, and the reaction time was 36 h.
[0096] Embodiment 15
[0097] The preparation of PA-66-based carbon dots was carried out in a similar manner to Example 1, except that the amount of 50% glutaraldehyde added was 400 μL, and the reaction time was 48 h.
[0098] Comparative Example
[0099] The preparation of PA-66-based carbon dots was carried out in a similar manner to Example 1, except that 0.5 g PA-66 and 25 mL deionized water were added to a 50 mL hydrothermal reactor.
[0100] Experimental example
[0101] Experimental Example 1 TEM test
[0102] The morphology and structure of the polyamide-based carbon dots prepared in Example 13 were characterized by transmission electron microscopy. The test results are as follows: Figure 1 shown.
[0103] Depend on Figure 1 (a) It can be seen that the polyamide-based carbon dots are spherical, have good dispersion and no agglomeration, and the particle size distribution is uniform. Figure 1 The illustration in (a) is a high-magnification transmission electron micrograph of polyamide-based carbon dots. It can be seen from the figure that the polyamide-based carbon dots form a crystalline structure with a lattice spacing of 0.21 nm, which is consistent with the in-plane lattice spacing (100 plane) of graphene.
[0104] from Figure 1 As can be seen in (b), the particle size range of the polyamide-based carbon dots is 1.6 to 3.5 nm, with an average particle size of 2.6 nm.
[0105] Experimental Example 2 Infrared Test
[0106] The polyamide-based carbon dots prepared in Example 13 were characterized using a Nicolet Nexus 670 infrared spectrometer with a scanning range of 4000-400 cm -1 , the number of scans is 64. The test results are as follows Figure 2 shown.
[0107] from Figure 2 It can be seen that at 3290cm -1 The absorption peak is the characteristic absorption peak of OH and also the stretching vibration of NH. Since the NH stretching vibration absorption band is weaker than that of OH stretching vibration and the spectrum band is sharper, the NH stretching vibration absorption band is covered by the OH stretching vibration. -1 The absorption peak is the stretching vibration of the secondary amide NH, and a hydrogen bond is formed. -1 and 2850cm -1 The absorption peaks at 1630cm are saturated CH asymmetric stretching vibration and saturated CH symmetric stretching vibration, that is, methylene asymmetric stretching vibration and methylene symmetric stretching vibration. -1 and 1540cm -1 The characteristic absorption peak at 1280cm is the C=O stretching vibration peak. The carbonyl (C=O) absorption band in imide presents a double peak due to vibration coupling. -1 The peak at 691cm is the CN stretching vibration peak of secondary amide. -1The peak at is the bending vibration peak of the OC=O group. From the infrared spectrum, we can see that the surface of carbon dots may contain polar functional groups such as -NH2, -COOH and -OH.
[0108] Experimental Example 3 Fluorescence Spectrum Test
[0109] The carbon dot solutions prepared in Examples 1 to 15 were diluted 100 times, and a certain volume of the above solutions was added to a four-way quartz cuvette for fluorescence spectrum testing. The excitation light wavelength was 365nm, and the widths of the excitation slit and the emission slit were both 2nm. The test results of Examples 1 to 4 and the comparative example are shown in FIG. Figure 3 As shown, the test results of Example 1 and Examples 5 to 9 are as follows Figure 4 As shown, the test results of Example 7 and Examples 10 to 12 are as follows Figure 5 As shown, the test results of Example 7 and Examples 13 to 15 are as follows Figure 6 The fluorescence lifetime of the carbon dots prepared in Example 13 was measured by fluorescence spectrometer, and the emission wavelength was 400 nm. After fitting, it was found that the fluorescence lifetime of the polyamide-based carbon dots was a double exponential fitting curve, with two radiation processes and luminescence centers. The test bar graph is shown in Figure 7 shown.
[0110] from Figure 3 It can be seen that the fluorescence intensity of the carbon dots prepared by using 50% glutaraldehyde as a cross-linking agent is much greater than that of the carbon dots prepared by using the same amount of other cross-linking agents.
[0111] Figure 4 In the figure, as the addition amount of 50% glutaraldehyde cross-linking agent gradually increases, the fluorescence intensity of polyamide-based carbon dots gradually increases, but when the addition amount of cross-linking agent reaches a certain amount, the fluorescence intensity of polyamide-based carbon dots is relatively stable, and the fluorescence intensity of polyamide-based carbon dots decreases as the cross-linking agent continues to be added.
[0112] Figure 5 In the experiment, with the increase of reaction temperature, the fluorescence intensity of carbon dots increases first and then decreases, and reaches the maximum at 240℃.
[0113] from Figure 6 It can be seen that with the extension of reaction time, the fluorescence intensity of carbon dots first increases and then decreases. At 24h, its fluorescence intensity reaches the maximum.
[0114] Figure 7 Among them, the lifetime of fluorescent component I is 4.42ns and the lifetime of fluorescent component II is 15.88ns, and the average lifetime is 13.57ns.
[0115] Experimental Example 4 Fluorescence quantum yield test
[0116] The absolute fluorescence quantum yield of the polyamide-based carbon dots prepared in Example 13 was tested. The excitation and emission slits of the fluorescence spectrometer were 4.3 nm and 0.43 nm respectively. The test results are as follows: Figure 8 As shown. The measurement of absolute fluorescence quantum yield is directly measured using the integrating sphere accessory, which is the ratio of the number of photons emitted by the fluorescent material after being excited to the number of photons of the excitation light absorbed. The inner surface of the integrating sphere is coated with a layer of highly reflective material (such as barium sulfate, polytetrafluoroethylene, etc.). The excitation light or emission light from all directions on the sample surface is homogenized by the integrating sphere and then emitted from the exit port and enters the monochromator and is finally detected by the detector. The measurement of absolute fluorescence quantum yield does not require a standard sample and the test process is simple, so it is increasingly used to characterize the luminous efficiency of fluorescent substances. In order to ensure the accuracy of the absolute fluorescence quantum yield during the test, the absorption of the tested sample at the maximum excitation wavelength should be less than 0.05.
[0117] Figure 8 In which EmScan Sample is the sample emission spectrum, EmScan Ref is the reference emission spectrum, and EmScan RefScaled is the corrected reference emission spectrum.
[0118] Figure 8 The intensity difference between the reference emission spectrum and the sample emission spectrum in the range of 330-350nm is the photons absorbed by the sample, and the intensity difference between the sample emission spectrum and the reference emission spectrum in the range of 350nm-600nm is the photons emitted by the sample. The ratio of the number of emitted photons to the number of absorbed photons is the fluorescence quantum yield. The fluorescence quantum yield of the polyamide-based carbon dots obtained in Example 13 is calculated to be 21.38%.
[0119] Experimental Example 5 Ion Selectivity Test
[0120] Prepare 10 mM of different metal salts (Cu 2+ Cr 3+ 、Zn 2+ , Ba 2+ , Fe 3+ , Ca 2+ 、Na + 、Cd 2+ , K + , Li + Mg 2+ , Fe 2 + , Pb 2+ 、Ag +Then, add 20 μL of the carbon dot solution prepared in Example 13 and 2 mL of deionized water to the cuvette, mix well and measure the emission spectrum at an excitation light wavelength of 340 nm, then add 20 uL of 10 mM different metal salt solutions respectively, ensure sufficient mixing and then let stand for 3 minutes, test the emission spectrum of the mixed solution at an excitation light wavelength of 340 nm by a fluorescence spectrometer, and calculate the change in fluorescence intensity before and after the addition of metal ions. Excitation wavelength 340 nm, excitation light slit 2 nm, emission light slit 2 nm. The test results are as follows Fig. 9 shown.
[0121] from Fig. 9 It can be seen that Fe 3+ The fluorescence quenching of PA-66-based carbon dots is most significant, and they hardly respond to other ions. 3+ Fluorescence detection.
[0122] Experimental Example 6Fe 3+ test
[0123] Anhydrous ferric chloride (FeCl3) was used to prepare FeCl3 at different concentrations (0.9, 4.9, 9.9, 19.7, 29.3, 39.2, 49.0, 58.5, 73.2, 98.0, 146.3 μmol / L, etc.) 3+ First, add 20 μL of the carbon dot solution prepared in Example 13 to the cuvette, then use a 5 ml pipette to transfer 2 mL of deionized water, mix the two evenly, measure the emission spectrum under the excitation of light with a wavelength of 340 nm, and then add different concentrations of Fe 3+ The solution was mixed evenly and then allowed to stand for 3 minutes. The emission spectrum was measured under light excitation at a wavelength of 340 nm, and the changes in fluorescence intensity before and after the addition of metal ions were recorded. 3+ Three sets of parallel data were measured at the same concentration, and the average value and standard deviation were calculated. The excitation wavelength was 340nm, the emission scanning range was 350-650nm, the fluorescence excitation slit was 2nm, and the emission slit was 2nm. The test results are as follows Fig.13 shown.
[0124] from Fig.13 It can be seen that in different Fe 3+ The fluorescence intensity of carbon dots is different at different concentrations. It can be seen that the fluorescence intensity of carbon dots is different from that of Fe 3+ The concentration is linear, and Fe 3+ The fluorescence quenching degree of PA-66-based carbon dots is linearly related, where R 2 The detection limit was 1 μM.
[0125] Experimental Example 7 pH Detection
[0126] The polyamide-based carbon dot solution obtained in Example 13 was diluted 100 times, and the pH of the solution was adjusted with 1 mol / L hydrochloric acid and 1 mol / L sodium hydroxide, and nylon-66-based carbon dot aqueous solutions of different pH values (pH = 2.6, 3.6, 4.7, 5.6, 6.6, 7.5, 8.6, 9.7, 10.7, 11.6, 12.6) were prepared respectively, and then 2.0 mL of the carbon dot aqueous solutions at different pH values were added to the fluorescence cuvettes, and the fluorescence spectra corresponding to each pH value were obtained by testing with a fluorescence spectrometer. The fluorescence spectrometer parameters are an excitation light wavelength of 340 nm, a scanning emission wavelength of 350-650 nm, a fluorescence excitation slit of 2 nm, and an emission slit of 2 nm. Three sets of parallel data were measured at each pH, and the average value and standard deviation were calculated. The test results are as follows: Fig.10 As shown, Fig.11 A graph showing the relationship between different pH values and the corresponding fluorescence intensity is shown.
[0127] from Fig.10 and Fig.11 It can be seen that the polyamide-based carbon dots exhibit different fluorescence intensities at different pH values. With the increase of pH, the fluorescence intensity gradually increases. The fluorescence intensity of the carbon dots is linearly related to the pH value. 2 The value is 0.9922, and thus the pH value of the solution can be estimated by the change in fluorescence intensity, indicating that the polyamide-based carbon dots prepared in the present invention can be used for pH detection.
[0128] Experimental Example 8 Stability Test
[0129] 5g of water-soluble starch was mixed with 20mL of PA-66-based carbon dot solution and placed in a 90℃ oven. Stirring was performed from time to time to ensure uniform mixing. After being thoroughly dried, the mixture was transferred to a mortar for grinding and the state of the ground powder was observed under natural light and 365nm ultraviolet light. The test results are as follows: Fig.12 shown.
[0130] Fig.12 It can be seen that the ground powder has brighter fluorescence under the irradiation of 365nm ultraviolet lamp, which means that the fluorescence intensity of polyamide-based carbon dots is not affected during the heating process, indicating that the optical properties of carbon dots are relatively stable.
[0131] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
Claims
1. A polyamide-based carbon dot, characterized in that: The polyamide-based carbon dots are prepared from polyamide and a cross-linking agent; The fluorescence intensity of the polyamide-based carbon dots is similar to that of Fe 3+ The concentration of is linearly related, and its fluorescence intensity is linearly related to pH value; The polyamide is polyhexamethylene adipamide (PA-66); The cross-linking agent is selected from one or more of hexachlorocyclotriphosphazene (HCCP), potassium perfluorobutylsulfonate (OSS), glutaraldehyde and concentrated phosphoric acid; The mass ratio of the cross-linking agent to the polyamide is (0.05-0.7):
1.
2. The polyamide-based carbon dots according to claim 1, characterized in that The mass ratio of the cross-linking agent to the polyamide is (0.1-0.6):
1.
3. The polyamide-based carbon dots according to claim 1 or 2, characterized in that: The particle size of polyamide-based carbon dots is 1 to 10 nm. -1 It has the characteristic absorption peak of OH and the stretching vibration peak of NH, 3060cm -1 The secondary amide NH stretching vibration peak is 2930 cm -1 and 2850cm -1 The absorption peaks at 1630 cm-1 are saturated CH asymmetric stretching vibration and saturated CH symmetric stretching vibration. -1 and 1540cm -1 The characteristic absorption peak at 1280cm is the C=O stretching vibration peak. -1 The peak at 691 cm is the CN stretching vibration peak of secondary amide. -1 The peak at is the bending vibration peak of the OC=O group.
4. A method for preparing the polyamide-based carbon dots according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: Step 1, mixing polyamide and a cross-linking agent and heating them to react; Step 2, filtering the product obtained in step 1 to obtain polyamide-based carbon dots; In step 1, The mass ratio of the crosslinking agent to the polyamide is (0.05-0.7):1; The reaction temperature is 150-350°C, and the reaction time is 5-60h.
5. The preparation method according to claim 4, characterized in that: In step 1, the mass ratio of the crosslinking agent to the polyamide is (0.1-0.6):
1.
6. The preparation method according to claim 4, characterized in that: In step 2, A syringe filter is used for filtration, and the pore size of the filter membrane is 0.1 to 0.8 μm.
7. An application of the polyamide-based carbon dots according to any one of claims 1 to 3 for preparing fluorescent ink, fluorescent powder, fluorescent agar gel, and for pH and Fe 3+ Content detection and anti-counterfeiting field.
